A Technology of Development of the Lawyer’s Psychogram and its Meaningful and Practical Component - RYZHIKOV, Vadim Stepanovich (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
Article concerns the psyhogram and characteristics as the basis for building a psychological portrait of a lawyer. According to modern ideas, the successful implementation of legal practice requires the harmonious combination of personal, intellectual, physiological, physiological and physical professionally important qualities. Our research resulted in identifying mental characteristics of a lawyer to be formed in the process of learning and building lawyer’s psyhogram (psychological profile), and we revealed the role of different professionally important qualities in future lawyer’s activity. Results of the research of accordance of psychological components of the lawyer’s professionalism are given in practical studies of the lawyer’s emotional and volitional spheres with average score of 4.68 according to the five-point scale, including 4.63 for normativity, 4.59 for communicability, 4.7 for selfconcept, and 4.68 for attitude to labor. Skills identified in the research are indexed 4.78 and comprise 4.79 for average memory, 4.76 for thinking, 4.7 for speech, and 4.7 for imagination. In the research participated more than 1,500 lawyers, students and graduate students of law. Accordingly, lawyer’s psychogram is included in a general architectonics system of professional training of future lawyers, who after a full course of study are practically ready for real professional activity.